The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.15406/ijcam.2017.07.00214
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Herbal Medicine in a Rural Community in Vitória Da Conquista, Bahia, Brazil: An Indication for Pharmacological Studies

Abstract: The present study evaluated ethno medicinal knowledge of people in the rural community of São Sebastião, Vitória da Conquista, Bahia, Brazil. Using semi-structured interviews, 84 randomly chosen individuals informed about the use of traditional medicinal plants in their community, thereby identifying their therapeutic potential, which were categorized according to the ICD-10 (International Statistical Classification of Diseases and Related Health Problems). The collected data were analyzed with using the Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…This is particularly important in most tropical countries where their rich plant biodiversity affords them the luxury to select from the plethora of plant resources with therapeutic potential. In developing countries, the use of plant medicine is the primary medical remedy for many people especially, among the rural population for treating and managing various disease conditions [ 1 ]. About 80 % of the world's population depends on herbal medicine because it is less costly, readily and easily accessible to consumers [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important in most tropical countries where their rich plant biodiversity affords them the luxury to select from the plethora of plant resources with therapeutic potential. In developing countries, the use of plant medicine is the primary medical remedy for many people especially, among the rural population for treating and managing various disease conditions [ 1 ]. About 80 % of the world's population depends on herbal medicine because it is less costly, readily and easily accessible to consumers [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In regards to the endemic and exotic herbs used in Brazilian folk medicine and complementary therapeutical practices, several species of "arnica" are noteworthy (Athayde et al, 2019;de Athayde et al, 2021;Marisco et al, 2017;Ribeiro et al, 2017), which are typically used as remedies in the form of tisanes; tinctures; bottled; globules; hot compresses; ointments; and gels. This range of formulations is accompanied by the therapeutical versatility of arnica, which is reported to treat: postoperative lesions such as bruises, sprains and abrasions; edema related to fracture and rheumatic pain of muscles and joints; inflammatory processes of the oropharynx; furunculosis; insect bites and stings; superficial phlebitis, etc (Athayde et al, 2019;Carvalho et al, 2018;Rodríguez-Chávez et al, 2017;Saraiva et al, 2015;Siqueira et al, 2018;Souza et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the leaves of S. purpurea have traditionally been used to treat gastritis (Borges & Moreira, 2016;Castro et al, 2011), hypertension (Silva et al, 2012;Marisco et al, 2017b) and diarrhea (Franco & Barros, 2006;Oliveira, Barros & Moita Neto, 2010;Freitas et al, 2012). Pharmacological studies have demonstrated its antimicrobial (Alencar et al, 2015;Miranda-Cruz et al, 2012;Marisco et al, 2017a;, antitumor , antioxidant and antiulcer potential (Almeida et al, 2017).…”
Section: Introductionmentioning
confidence: 99%